Thermal assessment of kpata fireclay for refractory applications - Amkpa, Job Ajala; Badarulzaman, Nur Azam (UR Publishers, 2018)
This study focused on the thermal propertiesof the Kpata fireclay in order to look into its refractoriness. Thermogravimetry (TGA), differential thermal analysis (DTA) and thermal conductivity tests were carried out to analyse the fireclay’s thermal properties. The fireclay was also compacted and fired at various firing temperatures. The TGA result indicated that there was material weight loss at 0.26 mg, 0.56 mg and 1.74 mg at temperatures of 90.53 °C, 425.12 °C and 578.87 °C respectively. The DTA revealed that there were exothermic and endothermic material reactions.The Kpata fireclay also had a thermal conductivity of 0.33 K (W/m.k). Apparent porosity of fired fireclay showed that the porosity was reduced as firing temperature increased. These conditions indicated that Kpata fireclay has the possibility in refractory and insulating applications.